Backward Design Model and Performance Tasks for Developing Speaking Skills in A1 EFL Learners - Morán Quiroga, Mónica Alejandra; Álvarez Llerena, Carlos Lenin; Bonilla Tenesaca, Josué Reinaldo; Egas Herrera, Diana Carolina (Arandu UTIC, 2025)
This study examined the effect of the Backward Design Model (BDM) and performance-based tasks on improving speaking skills among A1-level English as a Foreign Language (EFL) students at a private school in Ambato, Ecuador. An explanatory sequential mixed-methods design was applied, combining pre- and post-test assessments, self-assessment surveys, and observation checklists to evaluate students’ progress in fluency, pronunciation, vocabulary, grammar, confidence, and creativity. Performance tasks were developed using the GRASPS framework and aligned with WHERETO principles, both core components of BDM. These tools helped create structured and purposeful learning experiences that increased students’ engagement and oral performance. The findings showed that applying the BDM and its main components improved students’ speaking skills, revealing greater participation, more frequent use of English, and increased confidence while performing communicative tasks. Furthermore, students perceived the video-recorded role-play activities, based on the GRASPS framework, as an enjoyable and motivating task that encouraged creativity, repeated practice, and reduced speaking anxiety. Most of the students reported improvements in their speaking abilities and expressed a stronger willingness to use English in class. This research supports the pedagogical value of the BDM as a student-centered approach that promotes both linguistic development and learner autonomy. It emphasizes the importance of designing instruction around clear objectives and integrating meaningful, emotionally supportive activities into speaking lessons. Future studies are encouraged to examine the long-term effects of BDM and its applicability to other language skills and educational contexts.